Pasteurella multocida from outbreaks of avian cholera in wild and captive birds in Denmark - Pedersen, Karl; Dietz, Hans-Henrik; Jørgensen, J.C.; Christensen, T.K.; Bregnballe, T.; Andersen, T.H. (2003)
An outbreak of avian cholera was observed among wild birds in a few localities in Denmark in 2001. The highest mortalities were among breeding ciders (Somateria mollissima) and gulls (Larus spp.). Pulsed-field gel electrophoresis (PFGE) was conducted using ApaI and SmaI as restriction enzymes and restriction enzyme analysis (REA) using HpaII. The Pasteurella multocida subsp. multocida strain isolated from birds in this outbreak was indistinguishable from a strain that caused outbreaks in 1996 and 2003. Most isolates from domestic poultry had other PFGE patterns but some were indistinguishable from the outbreak strain. Among 68 isolates from wild birds, only one PFGE and one REA pattern were demonstrated, whereas among 23 isolates from domestic poultry, 14 different SmaI, 12 different ApaI, and 10 different HpaII patterns were found. The results suggest that a P. multocida strain has survived during several years among wild birds in Denmark.